2007
DOI: 10.17221/2270-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of fibre type distribution within muscle fascicles of pigs (Sus scrofa domestica)

Abstract: In order to determine breed differences in the fascicle structure of skeletal muscles, longissimus dorsi muscles (LD) and semimembranous muscles (SM), Duroc (D), Large White (LW), German Landrace (GL) and Swedish Landrace (SL) boars were analyzed. Fibre type delineation was based on the method of myofibrillar ATPase staining. The fibres in a fascicle were divided into layers according to their relation to the perimysium. In each layer, the proportions of fibre types I, IIA and IIB were determined and normalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
2
1
0
1
Order By: Relevance
“…Notably, fiber-typing studies indicated a degree of preferential type II fiber atrophy, in contrast to the reported mixed fiber atrophy typical of neurogenic atrophy in humans. This may be related to the baseline differences in muscle fiber type pattern and distribution in swine, which have previously been shown to vary with multiple factors including age and strain (77)(78)(79). Furthermore, some reports indicate regions with a baseline predominance of type II fibers, consistent with what we observed (77).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, fiber-typing studies indicated a degree of preferential type II fiber atrophy, in contrast to the reported mixed fiber atrophy typical of neurogenic atrophy in humans. This may be related to the baseline differences in muscle fiber type pattern and distribution in swine, which have previously been shown to vary with multiple factors including age and strain (77)(78)(79). Furthermore, some reports indicate regions with a baseline predominance of type II fibers, consistent with what we observed (77).…”
Section: Discussionsupporting
confidence: 88%
“…This may be related to the baseline differences in muscle fiber type pattern and distribution in swine, which have previously been shown to vary with multiple factors including age and strain (77)(78)(79). Furthermore, some reports indicate regions with a baseline predominance of type II fibers, consistent with what we observed (77). Thus, the observed differential atrophic fiber type response may be a swine-specific phenomenon.…”
Section: Discussionsupporting
confidence: 86%
“…The programme was successfully applied with human ( Pernuš and Eržen, 1991 ; Snoj-Cvetko and Eržen, 1992 ; Meznarič-Petruša et al , 1992 ; Pernuš and Eržen, 1994 ; Travnik et al , 1995 ; Čebašek et al , 1996 ; Eržen et al , 2000 ; Dahmane et al , 2001 ) and pig muscles ( Škorjanc et al , 2007 ), proving itself to be a useful tool. However, it was necessary to manually lay the photos on the tablet and all judgements were left upon the decision and experience of the human operator.…”
mentioning
confidence: 99%
“…Estudos têm sido realizados sobre o Sus scrofa domesticus no que se refere a órgãos urinários (FLETCHER, 1967), articulações (FUSS, 1991) e músculos (SKORJANC et al, 2007). No entanto, estudos pormenorizados utilizando a linhagem Dan Bred são escassos (França, 2015), especialmente no que se refere ao plexo lombossacral e seus ramos.…”
Section: Introductionunclassified